Urban Environment Factors and Neighborhood Satisfaction: Differences Between the Capital and the Interior of Paraná - Ramos-Esperidião, Aline; Lorenz-Fontolan, Beatrice; Iarozinski-Neto, Alfredo; Del-Roio, Iolanda Geronimo (Revista de Urbanismo, 2024)
Neighborhoods and cities must be designed with a focus on residents, and the importance of understanding their needs for urban planning is growing. Satisfaction with the urban environment has been studied without considering cities’ size, when certain neighborhoodrelated factors are analyzed. Therefore, this study investigates the differences between individuals who live in the capital of Paraná (Curitiba), and those who live in the interior of the State, in relation to the urban environment aspects. A sample of 282 respondents was collected through a questionnaire, and the data were analyzed using descriptive and multivariate statistics. Among other aspects, the satisfaction of Curitiba residents with the neighborhood is influenced by good commerce and green areas. For interior residents, satisfaction is more related to appearance. Still, the study highlights the importance of prioritizing alternative means of transport, such as walking.